Notice of Sculptured Stones found at 'Dinnacair', near Stonehaven - Thomson, Alexander (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author describes several carved stones that he recovered from where they were thrown into the sea in 1832. He covers what he knows of the stones' background and some information about the area in which they originated. The article includes some speculation as to what might have caused the stones to be at Dinnacair, but the author draws no conclusions.